UROLOGICAL COMPLICATIONS IN 350 CONSECUTIVE RENAL-TRANSPLANTS - SERT, S; GULAY, H; HAMALOGLU, E; HABERAL, M (WILEY, 1990)
Ten urological complications (2.9%) were found in 350 kidney transplants performed in this center. These included obstructive uropathy (20%), urinary leaks (40%), distal uretic fistulas (necrosis) (30%) and renal calculi (10%). Two grafts were lost due to chronic rejection 9 and 30 months post-operatively. The remaining 8 patients have stable renal function (mean creatinine 1.5 mg%). It was concluded that meticulous surgical technique may reduce the number of urological complications and early diagnosis and prompt surgical treatment may help to save the grafts.
Keywords: Urology & Nephrology